An organic transitional farm valuation, in Cipreses of Oreamuno, Cartago province: An investment proposal project - Montero Solís, Nataly (2019)
In order to estimate the value of a farm in Cipreses of Oreamuno, different valuation methods were implemented, as the econometric, comparative and financial method; thru a simple average the price per square meter was calculated in ₡6.182, for a total value of ₡47.392.188 in this 7.675,75 square meter property. Currently, the farm is cultivated with vegetables and is in a transition period to establish an organic production system. According to its land use capacity, it is classified as a “IIIe1c1” with a 9% slope in a premontane very wet forest. In this case of study, a greenhouse construction was taken into account for a total cost of ₡9.272.890, as three other infrastructures (a log house, a barn and a pond) as an investment project, increasing the property value in ₡106.657.646.